Environmental education in the treatment of urban solid waste and its socio-environmental impacts - Ulian, Marcelo Henrique Santana; Bin, Renan De Souza; Gomes, Vinicius Miguel; Nascibem, Fábio Gabriel (Universidade Estadual de Campinas, 2021)
The study presents the planning of a didactic sequence, proposed for the Didactics of Sciences discipline, on the teaching of Environmental Education, using as a generator theme the problem of consumerism and the generation of urban solid waste. The theme has great socio-environmental relevance, since most of the environmental and social problems are closely related to exacerbated consumption and, consequently, the generation of waste. In addition, it is deeply related to the reality of all students, since it is necessary to consume to survive and consumption generates waste. The methodology followed for the elaboration was the Three Pedagogical Moments, with the use of strategies such as Environment, Science, Technology, Society (ESTS) and the Dialogued Expository Class, among others. The sequence can awaken in students and teachers empathy for the environment and for environmental problems, stimulating conscious consumption, collectivism and a sustainable life.